2024
DOI: 10.1021/acsanm.3c05340
|View full text |Cite
|
Sign up to set email alerts
|

Long-Persistent High-Temperature Phosphorescence of Zero-Dimensional Metal Halide Hybrid for Temperature-Sensitive Anticounterfeiting

Yuerong Xie,
Juntao Peng,
Qianyang Qin
et al.

Abstract: Solid-state materials with long-persistence phosphorescence always suffer serious thermal quenching effect that greatly hinders their applications at high-temperature conditions (>373 K). Therefore, developing high-temperature phosphorescence (HTP) materials remains a great challenge. In this work, cytosine (Cyt) is hybridized with indium chloride into zero-dimensional (Cyt) 2 [InCl 5 • H 2 O] (CICH). A green afterglow up to 1.0 s is observed at room temperature for CICH but almost quenched at 448 K due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…As a kind of ionic compound, metal halide hybrids (MHHs) mainly consist of organic cations and metal halide polyhedra anions. Due to their wide composition and structure tunability, easy preparation, and excellent optical properties, MHHs have been attracted enormous attention in optoelectronic fields including X-ray scintillator, solid-state lighting, anticounterfeiting, information encryption, and stimulus response. , Recently, [2 + 2] photocycloaddition was successfully employed to control the room-temperature phosphorescence switch and photochromism in zero-dimensional (0D) bibased MHHs . Endowing MHHs with reversible photochromism could significantly broaden their applications in fields such as high-level-security information encryption and optical data storage.…”
Section: Introductionmentioning
confidence: 99%
“…As a kind of ionic compound, metal halide hybrids (MHHs) mainly consist of organic cations and metal halide polyhedra anions. Due to their wide composition and structure tunability, easy preparation, and excellent optical properties, MHHs have been attracted enormous attention in optoelectronic fields including X-ray scintillator, solid-state lighting, anticounterfeiting, information encryption, and stimulus response. , Recently, [2 + 2] photocycloaddition was successfully employed to control the room-temperature phosphorescence switch and photochromism in zero-dimensional (0D) bibased MHHs . Endowing MHHs with reversible photochromism could significantly broaden their applications in fields such as high-level-security information encryption and optical data storage.…”
Section: Introductionmentioning
confidence: 99%
“…That is, the external stimulation significantly changes the bond length and bond angle of the inorganic components, 29,30 the coordination number of metal ions, the coordination/insertion of the guest molecules, or the dimensional change of BX n m − . 31–42 For example, Xiao et al 43 reported that the bond length and bond angle of Sn 2+ -IOMHs C 4 N 2 H 14 SnBr 4 change significantly with increasing pressure, resulting in a larger dipole moment and higher structural and excited state distortion. Peng et al found that the hydrogen bond strength in [EtPPh 3 ] 2 [SbCl 5 ] can be influenced by diverse organic functional groups upon exposure to different organic gases.…”
Section: Introductionmentioning
confidence: 99%